UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TEKNIK KANCING GEMERINCING DI KELAS VIII5 SMP NEGERI 8 PEKANBARU - ', Santri; Yuanita, Putri; ', Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research is to improve the learning process and to improve mathematics achievement by applying the cooperative learning technique of jingling studs. The research is classroom action research (PTK) that consist of two cycles and at the end of every cycle carried out mathematics achievement test . The subject of this research is students of class VIII5 SMP Negeri 8 Pekanbaru in the second semester academic years 2015/2016, there are 36 students in the class, consist of 17 boys and 19 girls. Data collecting through observation and written test. The observation was doing for the observation of learning activity of teacher and students, of student’s attitude and of student’s skill. While written test which in daily test form was doing to evaluate student’s knowledge.Base on the result of analysis, the percentage of students passing the Minimun Completeness Criteria (MCC) on base score, daily test I (first cycle), daily test II (second cycle) were respectively 16,76%, 66,67%, and 75%. The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increase. The result of research conclude that applying the cooperative learning technique of jingling studs can improves the learning process and improves mathematics achievement of VIII5 SMP Negeri 8 Pekanbaru in the second semester academic years 2015/2016.Key words : Mathematics learning outcome, Cooperative learning technique of jingling studs, Classroom action research.